Music and Meaning: Sociological Interpretation of an Old Theme - Goštautienė, Rūta (Sociologija. Mintis ir veiksmas, 1997)
The aim of the article is to introduce the reader with John Shepherd, whose text fragments are republished in this journal issue. The article discusses the academic context of Shepherd’s project. It is argued that Shepherd’s work is best understood as an attempt to avoid the Scylla and the Charybdis of the scientific practice in the forms of post-structuralism and structuralism in the analysis of the phenomena.